Taxonomy and molecular systematics of the yellow-green grosbeak Caryothraustes canadensis (Passeriformes: Cardinalidae) - Tonetti, Vinicius Rodrigues [UNESP]; Bocalini, Fernanda; Silveira, Luís Fábio; Del-Rio, Glaucia (My University, 2017)
The Yellow-green Grosbeak Caryothraustes canadensis is a South American passerine occurring in Amazon and Atlantic Forests. Currently, it comprises four subspecies: Caryothraustes canadensis canadensis, Caryothraustes canadensis brasiliensis, Caryothraustes canadensis frontalis and Caryothraustes canadensis simulans. No study has ever revisited its taxonomy, hindering a complete understanding of the available diversity in Caryothraustes canadensis complex. We examined color and morphometric variation in 259 scientific specimens and sequenced the mitochondrial gene ND2 of 29 tissue samples. We also quantitatively and qualitatively analyzed 52 spectrograms of vocal recordings. Molecular analyzes demonstrated the existence of two divergent lineages in C. canadensis complex, one from Amazonia and the other in the Atlantic Forest, which can also be distinguished by morphometric and plumage characters. Here we propose that the C. canadensis complex is composed of two full species: C. canadensis and C. brasiliensis. Caryothraustes canadensis frontalis shows no reciprocal monophyly in the phylogenetic analyzes, despite having weak plumage diagnostic characters; therefore, we suggest it should be considered a synonym of C. brasilensis.
Keywords: Amazon; Atlantic forest; Genetic analysis; Oscines; Pernambuco endemism center; Phylogeny; Vocal analysis